Organizational behaviour - Robbins, Stephen P., 1943-; Judge, Tim; Campbell, Tim (New York, NY : Pearson Financial Times)
What is organizational behaviour? -- Foundations of individual behaviour -- Attitudes and job satisfaction -- Personality and values -- Perception and individual decision making -- Motivation concepts -- Motivation: from concepts to applications -- Emotions and moods -- Foundations of group behaviour -- Understanding work teams -- Communication -- Basic approaches to leadership -- Contemporary issues in leadership -- Power and politics -- Conflict and negotiation -- Foundations of organization structure -- Organizational culture -- Human resource policies and practices -- Organizational change and stress management.